Representation of functions of natural environment settings in the Kaba Minangkabau : an ecocritical study - Nofrahadi; Andayani; Suyitno; Nugraheni Eko Wardani (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research aimed to investigate the representation of functions of natural environment settings in the Kaba Minangkabau by using an ecocritical perspective. The natural environment in question was all living and non-living elements that occur naturally on Earth. Literary works stem from the love and admiration for the natural environment that fascinates, captivates, and inspires people with new perspectives to see the physical setting of everything they do. One form of literary work is the Kaba Minangkabau, a form of literature originating from the Minangkabau community that generally inhabits West Sumatra Province, Indonesia. This research was a qualitative study employing a phenomenological strategy. The research data were in the form of words, phrases, clauses, and sentences contained in the texts of Kaba Minangkabau, either delivered explicitly or implicitly and had undergone a translation process (from Minangkabau language to English). The sources of research data were the Kaba Minangkabau texts by Syamsudin Sutan Radjo Endah. The data were collected using reading and note-taking techniques. Data validation was conducted using a source triangulation. Data analysis was carried out involving interactive techniques, namely data reduction, data presentation, and conclusion drawing. Based on the study results, the following research findings were obtained. Eight data of natural environment settings were represented by the descriptions of sounds, events, and natural phenomena. Four natural environmentsettings were represented as literary references. Six natural environment settings were represented as analogies to the human physical forms.